Comparison on losses and flux distribution between two of 3 phase distribution transformer 1000kVA assembled with regular and irregular stack of transformer core lamination - Ismail, Daut; Dina Maizana, Maiz Ahmad; Shuhaimi, Zakaria; S. Uthman; Soib, Taib (Universiti Malaysia Perlis (UniMAP), 2008)
Organized by Universiti Malaysia Perlis (UniMAP), 15th - 16th March 2008 at Putra Brasmana Hotel, Perlis.